PENINGKATAN KUALITAS PEMBELAJARAN PKN MELALUI PENDEKATAN SOSIODRAMA PADA PESERTA DIDIK TINGKAT X SEMESTER 2 DI SMK N 4 SURAKARTA TAHUN PEMBELAJARAN 2010/2011 - Lastyawati, Sri Hastuti (2011)
Research purposes are (1) to describe civics learning process improvement with sociodrama method (2) to describe civics learning result improvement with sociodrama method. Research location is in X class, 2nd term at SMK 4 Surakarta. This research is class action research (PTK). Collecting data research has done by using method, observation, learning result and interview. Data analysis through three steps are: data reduction, data presentation, and conclusion/ verification. This in an active research with a PTK design. Research results are (1) improving student learning process quality pre cycle as 28%. Speech learning method is not giving support for student in study and learning process yet. Low student learning process quality in pre cycle because student boring of listening to the speech. Learning process quality in 1 cycle has improved as 16%, which enthusiasm student average pre cycle as 10 students (28%) in 1 cycle enthusiasm student average pre cycle as 16 students (44%). In sociodrama method learning process, student becomes more enthusiasm, because they are involved in learning process. Learning process quality improvement in 2 cycle as 19%. This improvement caused by teacher managed time efficiently, praise and punishment in education and addition mark for student can display drama well. (2) Civics learning result quality improvement in pre cycle includes average value as 7,4 and completeness as 16 students (44%). Low value in pre cycle activity caused by low student spirit. 1 cycle learning result improvement caused by higher spirit in study and learning process by using sociodrama compare to speech method. 2 cycle improvement showed by average value as 8,6 and completeness as 35 students (97%). It is caused by minimum completeness criteria (KKM) and spirit learning has been reach.